South-South and Triangular Cooperation in the Mexican Higher Education System - Didou Aupetit, Sylvie (International Journal of African Higher Education, 2018)
Academic collaboration in Mexico mainly follows a traditional pattern of North-South cooperation (primarily with the United States as well as some central European Union countries). Higher Education Institutions have also developed South-South cooperation in Latin and Central America and some are now exploring new opportunities in Asia, essentially with China, Japan and Korea. While there are fewer alternative schemes for student mobility, scientifc exchanges or joint degrees, innovative opportunities have emerged. It is important to consolidate such initiatives in light of the Trump administration’s position on migration that could negatively impact the current Mexican internationalisation model for higher education and research. La collaboration académique au Mexique suit principalement le schéma traditionnel d’une coopération nord-sud (principalement avec les EtatsUnis et quelques pays majeurs de l’Union Européenne). Les institutions d’enseignement supérieur ont aussi développé des coopérations sud-sud en Amérique centrale et latine, et certaines poursuivent aujourd’hui de nouvelles opportunités en Asie, essentiellement avec la Chine, le Japon et la Corée. Bien qu’il y ait peu d’alternatives à la mobilité étudiante, aux échanges scientifques ou aux diplômes communs, des approches novatrices émergent. Il est important de renforcer de telles initiatives étant donné la position du gouvernement de Trump sur l’immigration qui pourrait avoir un impact négatif sur le modèle actuel d’internationalisation de l’enseignement supérieur et de la recherche au Mexique.